A new syndrome: right-sided arcus aorta syndrome. (12th September 2013) - Ozkaya, Sevket; Dirican, Adem; Tuna, Tibel; Ece, Ferah
Abstract : Right-sided arcus aorta (RSAA) is a rare congenital anomaly that may cause chronic cough and dyspnoea. We aimed to define RSAA as a new syndrome characterised by RSAA, dyspnoea and cough during exercise. RSAA syndrome should be included in the differential diagnosis of asthma.